Does culture affect usability? A trans-European usability and user experience assessment of a falls-risk connected health system following a user-centred design methodology carried out in a single European country. (August 2018) - Stara, Vera; Harte, Richard; Di Rosa, Mirko; Glynn, Liam; Casey, Monica; Hayes, Patrick; Rossi, Lorena; Mirelman, Anat; Baker, Paul M.A.; Quinlan, Leo R.; ÓLaighin, Gearóid
Highlights: Technological devices often cannot meet the real needs of older adults. Negative user experience discourages older adults from using technology. User-Centered design (UCD) was employed in the development of WIISEL. Assessment of the usability of and user experience with WIISEL showed positive results. User-Centered design in one country results in positive usability in other countries. Abstract: Background: User-centred design (UCD) is a process whereby the end-user is placed at the centre of the design process. The WIISEL (Wireless Insole for Independent and Safe Elderly Living) system is designed to monitor fall risk and to detect falls, and consists of a pair of instrumented insoles and a smartphone app. The system was designed using a three-phase UCD process carried out in Ireland, which incorporated the input of Irish end-users and multidisciplinary experts throughout. Objective: In this paper we report the results of a usability and user experience (UX) assessment of the WIISEL system in multiple countries and thus establish whether the UCD process carried out in Ireland produced positive usability and UX results outside of Ireland. Methods: 15 older adults across three centres (Ireland, Italy and Israel) were recruited for a three-day trial of the system in their home. Usability and UX data were captured using observations, interviews and usability questionnaires. Results: The system was satisfactory in terms of the usability and UX feedback from the participants in all three countries. There was no statistically significant difference in the usability scores for the three countries tested, with the exception of comfort. Conclusions: A connected health system designed using a UCD process in a single country resulted in positive usability and UX for users in other European countries.